Health consequences of improving the content of ergothioneine in the food supply - Beelman, Robert B.; Phillips, Allen T.; Richie, John P.; Ba, Djibril M.; Duiker, Sjoerd W.; Kalaras, Michael D. (FEBS letters, 2022)
Ergothioneine (ERGO) is a potent antioxidant and anti‐inflammatory amino acid that is highly bioavailable to humans from the diet. ERGO is now regarded by some as a ‘longevity vitamin’ that has the potential to mitigate some chronic diseases of ageing and thereby increase life expectancy when present in adequate amounts. However, only limited knowledge exists regarding ERGO content in the human diet. Since ERGO is produced primarily by fungi, mushrooms are known to be the leading dietary source, but ERGO is found in relatively low amounts throughout the food chain as a result of soil‐borne fungi or bacteria passing it on to plants through their roots. Some conventional agricultural practices that negatively impact soil fungi, such as excessive soil disturbance (ploughing), can significantly reduce ERGO content of food crops when compared to regenerative practices such as eliminating tillage of the soil (no‐till). This has led us to the concept that ERGO may be a definitive connection between soil health and human health. Ergothioneine (ERGO) is a potent antioxidant and anti‐inflammatory amino acid considered a longevity vitamin able to mitigate some chronic diseases of ageing. Produced primarily by soil fungi and concentrated in mushrooms, ERGO is found in small amounts throughout the food chain. Aggressive agricultural practices (soil tilling) may reduce the level of ERGO found in food crops.